MATERNAL AND FOETAL OUTCOME IN CESAREAN HYSTERECTOMIES PERFORMED FOR PLACENTA INCRETA - Fawad, Anisa (Journal of Ayub Medical College Abbottabad, 2019)
Background: Placenta accreta is a serious obstetrical complication and is currently a very important indication for peripartum hysterectomy. The purpose of this study is to review the frequency of Caesarean hysterectomies performed for placenta accreta and maternal, foetal outcome of these patient. Methods: In this cross-sectional study all the patients who underwent emergency hysterectomies for different obstetrical indications during this one year were included in this study. Among them the hysterectomies performed for massive antepartum haemorrhage due to placenta increta were reviewed in detail and risk factors were identified. Results: Caesarean hysterectomies performed for different obstetrical indications were 47 and 10 were due to placenta previa increta (21.2%). The mean age of the patients was 30±5.5 years. Majority of the patients were multigravidas between 26 and 35 years of age. 30% of patients were Para-3 and 70% of patients were Para-4 and above. 01 patient (10%) had previous one Caesarean section with placenta previa increta, 02 patients (20%) had previous 02 C-Sections and low-lying placenta adherent to it and 04 patients (40%) had previous 03 C-Sections and major degree placenta previa and 03 patients (30%) had 04 C-Sections with placenta increta. Among the foetal outcome 04 babies (40%) were delivered between 28-32 weeks of gestation. 05 foetuses (50%) were delivered between 33-36 weeks of gestation and one foetus (10%) was delivered at term. 02 babies delivered at 28 weeks of gestation had early neonatal death due to prematurity. There were no maternal deaths in this time period. Conclusion: placenta previa increta is a major obstetrical complication. Timely recognition and delivery in a tertiary care hospital with surgical expertise, blood bank facilities and intensive care facilities both for the mother and the baby are needed to improve maternal and foetal outcome. Keywords: Placenta previa; Placenta accrete; Placenta increta; Hysterectomy, Maternal mortality, Maternal morbidity